Drug Metabolizing Enzymes: Cytochrome P450 and Other Enzymes in Drug Discovery and Development - Jae S Lee [ editor ] (CRC Press / Taylor & Francis, 2003)
Critical in the elimination of drugs and other xenobiotics from the body, cytochrome P450 has strong bearing on scientific assessments of genetic polymorphism in metabolism, possible drug-drug interactions, and bioavailability of candidate drugs. This text systematizes findings on P450 and similar enzymes - as well as parallel issues shaping the pharmaceutical industry - to promote the next generation of safer, more effective drugs.